Low-emission development of rice production in Vietnam: Lessons learned from scaling of alternate wetting and drying in the red river delta - Sander, Björn Ole (2018)
Presentation by B. Ole Sander, International Rice Research Institute or research supported by CCAFS, the Climate and Clean Air Coalition, and USAID International conference on agricultural emissions and food security: Connecting research to policy and practice 10-13 September 2018 Berlin, Germany